Evaluation of free radical-scavenging and antihemolytic activities of quince (Cydonia oblonga) leaf: A comparative study with green tea (Camellia sinensis) - Costa, Rossana M. (2011)
This study aimed to determine the phenolic profile and to investigate the antioxidant potential of quince (Cydonia oblonga) leaf, comparing it with green tea (Camellia sinensis). For these purposes, methanolic extracts were prepared and phenolics content of quince leaf was determined by HPLC/UV. The antioxidant properties were assessed by Folin–Ciocalteu reducing capacity assay and by the ability to quench the stable free radical 2,20-diphenyl-1-picrylhydrazyl (DPPH) and to inhibit the 2,20-azobis(2-amidinopropane) dihydrochloride (AAPH)-induced oxidative hemolysis of human erythrocytes. 5-O-Caffeoylquinic acid was found to be the major phenolic compound in quince leaf extract. Quince leaf exhibited a significantly higher reducing power than green tea (mean value of 227.8 ± 34.9 and 112.5 ± 1.5 g/kg dry leaf, respectively). Quince leaf extracts showed similar DPPH radical-scavenging activities (EC50 mean value of 21.6 ± 3.5 lg/ml) but significantly lower than that presented by green tea extract (EC50 mean value of 12.7 ± 0.1 lg/ml). Under the oxidative action of AAPH, quince leaf methanolic extract significantly protected the erythrocyte membrane from hemolysis in a similar manner to that found for green tea (IC50 mean value of 30.7 ± 6.7 and 24.3 ± 9.6 lg/ml, respectively, P > 0.05). These results point that quince leaf may have application as preventive or therapeutic agent in diseases in which free radicals are involved.